Association between parenting styles and perception of family functioning in adolescent mothers - Castillo Uparela, Laura; Fonseca-Beltrán, Leodanis; Doria Davila, Daniela (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The objective of this paper is to analyze the relationship between parenting styles and the perception of family functioning in pregnant adolescents in rural areas of the department of Sucre (Colombia). This is a quantitative correlational study. The results show that 42.5% of the sample identified with the negligent style, while 20.87% of the participants identified with the authoritative parenting style. The authoritative and permissive parenting styles were positively related to a good perception of family function. Neglectful parenting style is negatively related to a good perception of family function.